A Scientific Reading of the Protagonists Tragedy in Thomas Hardys Tess of the Durbervilles - Choedphong Uttama (My University, 2016)
Thomas Hardy’s novels are known for the portrayal of their protagonists’ ill fortune and tragedies. Attempts have been made to understand the pessimism that pervades his novels through the study of the harsh life of the rural proletariat, the class into which many of his protagonists fall, or of Victorian society itself which, with its forms of social constraint, limited people’s life and was a cause of unhappiness. This paper offers an alternative way of understanding the pessimism in Tess of the d’Urbervilles (1891) through a scientific reading of the protagonist’s tragic life. By contextualizing this novel in the Victorian period when advances in science challenged religious belief and by considering the author’s interest in science and his ambivalent attitude towards religion, this paper aims to show that the calamitous life of the protagonist can be explained by the theory of natural selection in which living things are controlled by chance and randomness as opposed to religious belief which holds that God is behind human destiny. This reading also ties in with the theory and power of heredity which denies the individual any real choice, making the protagonist unable to control her own actions. The last approach will look at mesmerism which can shed light on the most important and controversial scene in the novel and which greatly contributes to the protagonist’s tragedy.
Keywords: Destiny (ISS module); Tragedy (event); Ambivalence; Proletariat; Pessimism; Thomas Hardy Literature Studies